PHONOLOGICAL ACQUISITION OF A CHILD SUFFERING FROM LANGUAGE DELAY - Naibaho, Lamhot (PPs UNJ, 2016)
This study deals with language acquisition which investigates the phonological acquisition of a child suffering from language delay. A case study design with cross-sectional survey type is used and it was conducted at Jl. Ujung Serdang, Komp. Cendana Asri No 21 Tanjung Morawa Medan, North Sumatera Indonesia, where a five year old child was chosen to be the subject. In collecting the data, this study applies documentation with audio visual recorder as the instrument of collecting data and the technique of data analysis used in this study was descriptive technique, then the data were described through the process of transcribing and reducing the data by the process of selecting, focusing, simplifying, transforming the transcripts of the data, then displaying the data and finally drawing the conclusions. The findings indicate that the subjects of this study who suffers from language delay in his five year old had mastered vocabularies covering noun, adjective, verb, and adverb, and the data show that he acquired more noun comparing to adjective, verb and adverb. In case of phonological acquisition, seven phonological processes were found: stopping process, fronting process, voicing process, clustering reduction process, deleting of final consonant process, deleting of unstressed process and reduplicating process. In expressing the language in his daily life, sometimes he used the body language to help him deliver the message.